Transformational leadership from the Bhagavad-Gita and the significance for human capital development - Muniapan, Balakrishnan; Rajantheran, M. (2008)
The significance of transformational leadership has received great deal of attention in the leadership literature during the last two decade as the current business environment requires organizational leaders to be transformational. This is also due to several studies, which have been done in this area, leading to a wider recognition that transformational leadership style is extremely essential for organizational growth and development as it is the quality of the leaders and their leadership determines the quality of the organizations. In this paper, an attempt has been made by the authors to explore transformational leadership from an ancient Indian Vedic philosophy and provide the significance to human capital development. A review of literature in transformational leadership shows that there are thousands of articles which have been written by several academics on this subject from numerous perspectives, but limited articles have been written from the philosophical perspectives. As a result, this paper not only fills the gap in the literature of transformational leadership, but also provides some significance and insights on human capital development from the ancient Indian Vedic philosophical perspective. For this purpose, the authors have selected the Bhagavad-Gita, which provides the essence of the Indian Vedic thought to explore transformational leadership concepts for human capital development. This paper is based on hermeneutics, a qualitative research methodology which involves study, understanding and interpretation of ancient or classical text. The Bhagavad-Gita is more than 5,000 years old and is written in Sanskrit language. In a nutshell, the Bhagavad-Gita provides an inside-out approach to leadership and human capital development which is the self leadership first before leadership of every other thing. The organizational leaders are advised to firstly conquer the enemies within such as desires, anger, greed,arrogance, infatuation, envy, pride or ego and foolhardiness as it is often said that a leader who conquers the enemies within will be able to conquer his self and also others. The prospects of analysis of the Bhagavad-Gita in other areas of organizational leadership such as strategic management, organizational behavior, human resource management and employment relations can be considered for future research.